Clinical course of left spatial neglect with a focus on the assessment of stimulus-driven attention. Issue 6 (2nd November 2021) - Motomura, Kazuya; Amimoto, Kazu
ABSTRACT: We developed Stimulus-driven Attention Tests (SAT) for a patient with unilateral spatial neglect (USN) and longitudinally investigated the results and compared them to two conventional assessments. The patient suffered a right putaminal hemorrhage resulting in left-side USN. On the 12th, 22nd, and 28th days from the onset, the Behavioral Inattention Test (BIT) and the Catherine Bergego Scale (CBS), which are conventional USN assessments, and our two Stimulus-driven Attention Tests (SAT-1 and SAT-2) were performed. Our assessment tests comprise two tasks in which participants respond to suddenly appearing stimuli and to a target stimulus among distractors. A longitudinal comparison of all assessments was performed to observe the clinical course of the USN. On the 12th day, scores were low on the BIT, CBS, and both SATs, but on the 22nd day, BIT improved above the cutoff; however, the CBS and SATs did not improve. On the 28th day, response to a target stimulus among distractors in the SAT remained low, and CBS scores did not change significantly. We were able to detect USN with the SAT when the participant showed improvement on the paper-and-pencil tests. Moreover, the number of distractors in the SAT was thought to reveal covert USN.